2005
DOI: 10.1098/rsta.2004.1485
|View full text |Cite
|
Sign up to set email alerts
|

Halocarbon and dimethyl sulphide studies around the Mascarene Plateau

Abstract: Air-sea exchange is thought to be one of the major routes by which halocarbons and dimethyl sulphide reach the troposphere and stratosphere. Once there, in different ways, they participate in chemical reactions that have implications for ozone depletion and climate change. The gases are released by phytoplankton and other algae, but our present understanding of the sources and sinks is insufficient to establish a balanced global budget. Published data suggest that there are regions of coastal and ocean waters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 42 publications
2
15
0
Order By: Relevance
“…CH 3 I (0.84 ± 0.12 ppt) mixing ratios reveal pronounced variations and surpass 1 ppt in some locations. These atmospheric mixing ratios above the open ocean are much lower than the average of 12 pptv Smythe-Wright et al (2005) reported around the Mascarene Plateau.…”
Section: Vsls Observations and Oceanic Emissionsmentioning
confidence: 59%
See 1 more Smart Citation
“…CH 3 I (0.84 ± 0.12 ppt) mixing ratios reveal pronounced variations and surpass 1 ppt in some locations. These atmospheric mixing ratios above the open ocean are much lower than the average of 12 pptv Smythe-Wright et al (2005) reported around the Mascarene Plateau.…”
Section: Vsls Observations and Oceanic Emissionsmentioning
confidence: 59%
“…A few measurements in the Bay of Bengal (Yamamoto et al, 2001) and Arabian Sea (Roy et al, 2011) as well as global source estimates suggest that the Indian Ocean might be a considerable source (Liang et al, 2010;Ziska et al, 2013). No bromocarbon data are available for the equatorial and southern Indian Ocean, yet, but CH 3 I, which has been measured around the Mascarene Plateau, showed high oceanic concentrations (Smythe-Wright et al, 2005). Liang et al (2014) use a chemistry climate model for the years 1960 to 2010 and modeled that the tropical Indian Ocean delivers more bromine to the stratosphere than the tropical Pacific because of its higher atmospheric surface concentrations based on the global top-down emission estimate by Liang et al (2010).…”
mentioning
confidence: 99%
“…The olfactory capsules in R. typus are spherical and moderately large (Dennison, 1937) which Martin (2007) suggested would have similar chemo‐sensory detection abilities to those of the nurse shark Ginglymostoma cirratum (Bonnaterre 1788). While plankton per se may not have an identified scent, seabirds find areas of high plankton productivity by following dimethyl sulphide (DMS) given off when phytoplankton are grazed by herbivorous zooplankton (Nevitt et al , 1995; Smythe‐Wright et al , 2005). As DMS is soluble in water, it could also be a good scent trail for R. typus ; while no research has been undertaken in this field some correlational insights are available.…”
Section: Biology Ecology and Habitsmentioning
confidence: 99%
“…In general, ocean concentrations range from zero to <5 ng L −1 , although there are some notable exceptions. For example diiodomethane concentrations as high as 190 ng L −1 have been observed in Swedish coastal waters [ Klick and Abrahamsson , 1992], methyl iodide concentrations of up to 7.0 ng L −1 in the tropical and subtropical waters of the Western Atlantic, Central Indian and East Pacific Oceans [ Smythe‐Wright et al , 2005, 2006; Singh et al , 1983] and 8.0 ng L −1 in coastal waters [ Moore and Tokarczyk , 1993], bromoform concentrations of up to 50 ng L −1 in Arctic and Antarctic Waters [ Schall and Heumann , 1993; Reifenhauser and Heumann , 1992] and methyl chloride up to 8 ng L −1 in the North West Atlantic in summer [ MacDonald and Moore , 2007]. The sources and sinks of these organohalogens are unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Phytoplankton produce a wide range of organohalogens. There is evidence for the release of the methyl halides, CH 3 Br, CH 3 Cl and CH 3 I [ Manley and de la Cuesta , 1997; Moore , 2003; Saemundsdóttir and Matrai , 1998; Smythe‐Wright et al , 2005, 2006]. Other workers have shown the production of more complex compounds such as CHBr 2 Cl, CH 2 Br 2 , CH 2 BrI, CHBr 3 , CHCl 3 , CH 2 ClI, CH 2 I 2 , C 2 H 5 I, C 2 Cl 4 and C 2 HCl 3 [ Moore , 2003; Abrahamsson et al , 1995].…”
Section: Introductionmentioning
confidence: 99%